Le sens des mots : le vocabulaire du genre en Espagne - Sofía Rodríguez (Amnis)
In these lines there is an account of gender studies in Spain and the key concepts on which this research has pivoted. The aim of this article is to show the relationship between the evolution of feminist theory and the gradual emergence of a vocabulary that explain women as political subjects. If power relationships are the epicenter of the categories of historical analysis, violence, social demands and maternalism are on the street and the agendas of state. But the future brings new challenges and intercultural dialogue, no doubt, will expand or transform the discourse of women and gender language in the XXI century.